Trends in Emergency Peripartum Hysterectomy at a Single Institution: 1988–2009 - Hernandez, Jennifer S.; Wendel, George D., Jr.; Sheffield, Jeanne S. (American Journal of Perinatology, 2013)
Objective To evaluate trends of emergency peripartum hysterectomy over two decades.Study Design This was a retrospective cohort study of peripartum hysterectomies at one institution from 1988 to 2009. Medical records were reviewed and data from the first 11 years were compared with data from the second 11 years.Results During the study period, 558 emergent peripartum hysterectomies were performed with full records available for 553 to review: 280 in the first period, 273 in the second (p = 0.19). In the second period, prior cesarean deliveries, length of surgery, estimated blood loss, blood transfusions, and the number of units transfused were all increased (p < 0.001). Also in the second period, there were twice as many hysterectomies for suspected placental invasion, and an almost threefold increase in pathologically confirmed placental invasion (both p < 0.001).Conclusion Although emergent peripartum hysterectomies are not increasing in frequency, the risk factors and morbidities have changed.
Keywords: cesarean deliveries; emergency peripartum hysterectomy; placental invasion